2018
DOI: 10.1186/s12911-018-0596-8
|View full text |Cite
|
Sign up to set email alerts
|

An openEHR based approach to improve the semantic interoperability of clinical data registry

Abstract: BackgroundClinical data registry is designed to collect and manage information about the practices and outcomes of a patient population for improving the quality and safety of care and facilitating novel researches. Semantic interoperability is a challenge when integrating the data from more than one clinical data registry. The openEHR approach can represent the information and knowledge semantics by multi-level modeling, and it advocates the use of collaborative modeling to facilitate reusing existing archety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…This study focused on describing the development process of openEHR archetype-based structures, used to represent cancer clinical statements proposing nutritional care. These archetypes can be used to improve EHR interoperability [40]. Some authors have suggested that EHRs have a strong potential to improve cancer outcome research [41] and patient care [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focused on describing the development process of openEHR archetype-based structures, used to represent cancer clinical statements proposing nutritional care. These archetypes can be used to improve EHR interoperability [40]. Some authors have suggested that EHRs have a strong potential to improve cancer outcome research [41] and patient care [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on describing the development process of openEHR archetype-based structures, used to represent cancer clinical statements proposing nutritional care. These archetypes can be used to improve EHR interoperability [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, better retrieval results could help users to identify reusable archetypes quickly, promote reuse of archetypes, and improve standardization of CIMs, thereby enhancing interoperability of EHRs. Archetype modeling methodology [15,23] showed that clinicians and domain experts should compare archetype design specifications with retrieved archetypes to decide whether new archetypes need to be developed or whether an existing one could be adapted. Our method could successfully identify relevant archetypes that the CKM could not find, such as “openEHR-EHR- SECTION.problems_and_diagnoses.v1” in the diagnosis retrieval task.…”
Section: Discussionmentioning
confidence: 99%
“…The stockholders of health systems include clinicians, healthcare organizations, patients, device, or manufacturers. Establishment of semantic interoperability needs the involvement of all stockholders [20,21].…”
Section: Background and Rationalementioning
confidence: 99%